Bearing Life Evaluation in Between Bearing Centrifugal Pumps: Evaluasi Umur Bantalan pada Pompa Sentrifugal dengan Bantalan - Dewanto, Dodik Hari; Fahruddin, A’rasy (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Centrifugal pumps are widely applied in industrial cooling systems where bearing reliability determines operational continuity. Specific Background: At PT Java Pacific, a between bearing centrifugal pump using type 6311 deep groove ball bearing operates for gearbox cooling and frequently experiences premature failure. Knowledge Gap: A discrepancy exists between theoretical bearing life estimation and actual service life in field operation, yet quantitative comparison in this specific configuration remains limited. Aims: This study aims to calculate the theoretical L10h bearing life, compare it with actual operational data, and formulate an appropriate preventive maintenance strategy. Results: Based on a basic dynamic load rating of 74.1 kN, equivalent load of 5.45 kN, and shaft speed of 5000 rpm, the calculated bearing life is 8,378.07 hours (0.96 years). However, field data show replacement intervals of only 5–8 months, indicating earlier degradation primarily associated with lubrication and operational factors. Novelty: This study provides a direct quantitative comparison between theoretical bearing life and real industrial data for a 6311 bearing in a between bearing centrifugal pump configuration. Implications: The findings support structured lubrication scheduling and condition monitoring to reduce premature bearing failure and optimize maintenance planning in industrial pump systems. Keywords: Centrifugal Pump, Bearing Life, Preventive Maintenance, Equivalent Load, Industrial Reliability Key Findings Highlights Theoretical L10h calculation produced 8,378.07 operating hours under specified load and speed conditions. Field replacement records indicate shorter service intervals of 5–8 months. Lubrication management and operational load control are critical factors in reducing premature failure.